2022
DOI: 10.1002/aelm.202200810
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐Controlled Artificial SiZnSnO/P(VDF‐TrFE) Synaptic Devices with a High Dynamic Range for Neuromorphic Computing

Abstract: Artificial synapses, such as ferroelectric field‐effect transistors, aspire the brain‐like computation in real life and are likely to replace conventional computing methods in the future. Amorphous SiZnSnO (a‐SZTO)‐based ferroelectric field‐effect transistor is fabricated using the organic poly(vinylidene fluoride‐trifluoroethylene) P(VDF‐TrFE) ferroelectric gate insulating layer. First, the ferroelectric properties of P(VDF‐TrFE) are analyzed depending on the crystallization temperature for artificial synapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…As shown in Figure f, the maximum recognition rate for our FeFET synaptic device was 85.4%, which is comparable to previous studies on other synaptic devices (see Supporting Information Table S2). …”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure f, the maximum recognition rate for our FeFET synaptic device was 85.4%, which is comparable to previous studies on other synaptic devices (see Supporting Information Table S2). …”
Section: Resultsmentioning
confidence: 99%
“…Overall, increasing the thickness of the LATP layer improved the linearity characteristics of the conductance modulation, resulting in a higher pattern recognition accuracy and stability in neuromorphic systems with on-chip learning. Finally, to compare the synaptic characteristics of our synaptic transistors with those of other inorganic semiconductor-based synaptic transistor devices, the nonlinearity values and recognition accuracy obtained in this study and recently reported studies are summarized in Table . Compared with other studies, the proposed device exhibits better linearity characteristics and a high pattern recognition accuracy (94.53%) owing to the optimization of the LATP layer with a high ionic conductivity.…”
Section: Resultsmentioning
confidence: 85%
“…The first approach controlled the carrier density of a semiconducting channel using the polarization field from a ferroelectric material. [33,34,[36][37][38][39][119][120][121][122][123][124] We note that ferroelectric materials have certain domains that have different polarization directions along their easy axis. The continuous change in the polarization field from the ferroelectric domains enables multiple conductivity states in the semiconducting channel, which can be used as a synaptic device and learning process.…”
Section: Ferroelectric Gating Of 2d Semiconducting Channelsmentioning
confidence: 87%